1990
DOI: 10.2527/1990.6892945x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzed feather meal as a protein source for growing calves.

Abstract: Growth, digestion and in situ studies were conducted to determine the protein value of hydrolyzed feather meal (Fth) for growing ruminants. Dacron bags containing blood meal (BM), Fth, corn gluten meal (CGM) and soybean meal (SBM) were suspended in the rumen of two steers for 12 h to estimate escape protein. The escape protein value for Fth, 69.1%, was less than that for BM (82.8%) and CGM (80.4%; P less than .05) but greater than that for SBM (26.6%; P less than .05). Apparent protein digestion by lambs was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 17 publications
5
19
0
Order By: Relevance
“…The increase in concentration of other essen- tial amino acids may be due to preferential bacterial degradation of nonessential amino acids and nucleic acids in the rumen. Although Weakley et al (1984) and Goedeken et al (1990) reported that amino acid profiles were not altered extensively during in situ incubation, this work agrees with that of Varvikko (1986) and Crooker et al (1981), who reported certain amino acids were more resistant to degradation than others. Amino acid concentrations before incubation were poorly correlated to amino acid concentrations after incubation (Table 6), with the exception of methionine, isoleucine, and lysine, which were highly correlated ( r = .97, .75, and .64, respectively, P < .05).…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…The increase in concentration of other essen- tial amino acids may be due to preferential bacterial degradation of nonessential amino acids and nucleic acids in the rumen. Although Weakley et al (1984) and Goedeken et al (1990) reported that amino acid profiles were not altered extensively during in situ incubation, this work agrees with that of Varvikko (1986) and Crooker et al (1981), who reported certain amino acids were more resistant to degradation than others. Amino acid concentrations before incubation were poorly correlated to amino acid concentrations after incubation (Table 6), with the exception of methionine, isoleucine, and lysine, which were highly correlated ( r = .97, .75, and .64, respectively, P < .05).…”
Section: Methodssupporting
confidence: 81%
“…Ruminal incubation of these protein sources increased essential amino acid concentration ( P < .05) as a ratio of the CP escaping ruminal degradation (Table 6), with the exception of tryptophan, which decreased in concentration. This decrease in tryptophan, also observed by Goedeken et al (1990), suggests preferential degradation of tryptophan in the rumen. The increase in concentration of other essen- tial amino acids may be due to preferential bacterial degradation of nonessential amino acids and nucleic acids in the rumen.…”
Section: Methodsmentioning
confidence: 85%
“…Goedeken et al (1990) reported an AA profile of corn gluten meal expressed as a percentage of CP of 4.3% Arg, 1.9% His, 4.2% Ile, 16.5% Leu, 1.8% Lys, 2.7% Met, 6.6% Phe, 3.7% Thr, and 4.5% Val after 12 h of ruminal incubation. MacDonald (2006) reported an AA profile of DDG expressed as a percentage of CP of 7.5% Arg, 4.2% His, 2.6% Ile, 10.4% Leu, 2.6% Lys, 1.4% Met, 3.2% Phe, 3.3% Thr, and 3.7% Val after 16 h of ruminal incubation.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 As a result, other animal proteins such as blood (rich in lysine) may need to be added to enhance the nutritional quality of the product. 9,10 Even with processing, it is priced similar to other feedstuffs, ie soybean meal, with half the protein level. Low solubility and amino acid imbalance limits its use in non-ruminants in poultry 5 and swine.…”
Section: Introductionmentioning
confidence: 99%